Inbreeding among Caribbean Hispanics from the Dominican Republic and the Effects on the Risk of Alzheimer's Disease - Vardarajan, BN (Genet Med, 2014)
BACKGROUND: Inbreeding can be associated with a modification in disease risk due to excess homozygosity of recessive alleles impacting a wide range of phenotypes. We estimated the inbreeding coefficient in Caribbean Hispanics and examined its effects on risk of late-onset Alzheimer's Disease (LOAD). METHODS: The inbreeding coefficient was calculated in 3392 subjects (1451 LOAD patients and 1941 age-matched healthy controls) of Caribbean Hispanic ancestry using 177,997 nearly independent SNPs from genome-wide array. The inbreeding coefficient was estimated using the excess homozygosity method with and without adjusting for admixture. RESULTS: The average inbreeding coefficient in the Caribbean Hispanics without accounting for admixture was F=0.018 (±0.048) suggesting a mating equivalent to second cousins or second cousins once removed. Adjusting for admixture from 3 parent populations, the average inbreeding was found to be 0.0034 (±0.019) or close to third cousin mating. Inbreeding coefficient was a significant predictor of AD when age, sex and APOE genotype was used as adjusting covariates (p=0.03). CONCLUSIONS: The average inbreeding in this population is significantly higher than the general Caucasian populations in North America. The high rate of inbreeding resulting in increased frequency of recessive variants is advantageous for the identification of rare variants associated with LOAD.